การสร้างกลยุทธ์ในการจัดการความรู้: Creating a Strategy to Manage Knowledge - ศรีพันธ์ อัจฉรา (Journal of Business, Innovation and Sustainability (JBIS), 2011)
Download files DOI: http://dx.doi.org/10.14456/becj.2011.8